Ondansetron Preloading with Crystalloid Infusion Reduces Maternal Hypotension during Cesarean Delivery - Wang, Qun; Zhuo, Lang; Shen, Ming-Kun; Yu, Yan-Yun; Yu, Jun-Jing; Wang, Meng (American Journal of Perinatology, 2014)
Objective The aim of the article was to investigate the effect of ondansetron preloading with crystalloid infusion after spinal anesthesia during cesarean delivery.Study Design A total of 66 parturient women scheduled for elective caesarean sections were randomly assigned to two groups. Five minutes before spinal anesthesia, Group O patients were injected with 4 mg of ondansetron, while Group S patients were injected with 5 mL physiological saline. Maternal blood pressure and heart rate were measured at 2 minute intervals for 30 minutes. After delivery, umbilical cord blood samples were analyzed.Results Maternal hypotension and nausea were significantly lower in ondansetron-treated patients versus placebo (p = 0.011 vs. 0.004). Umbilical venous pH was significantly higher in ondansetron-treated patients (p = 0.006), while partial pressure of carbon dioxide (Pco2) was significantly lower (p = 0.002). Decreases in maternal systolic and mean arterial blood pressures were significantly lower in ondansetron-treated patients (p = 0.008 vs. 0.025), with less requirement for phenylephrine administration compared with controls (p = 0.029).Conclusion Ondansetron preloading combined with crystalloid infusion significantly reduced hypotension and nausea, while improving acid–base status, as well as reducing vasoconstrictor use.
Keywords: ondansetron; hypotension; spinal anesthesia; cesarean delivery